Using social media for consumer interaction: An international comparison of winery adoption and activity - Gergely Szolnoki; Rebecca Dolan; Sharon Forbes; Liz Thach; Steve Goodman (Wine Economics and Policy, 2018)
With the rapid adoption of social media by consumers, it is increasingly important for retailers to investigate and consider their use and adoption of social media, and to know which activities are most effective. This can differ by product line and geographical location. Further, for complex products such as wine, with specific consideration of higher price segments, consumers frequently search for more information before purchase. This study investigates the social media adoption and activities of 1173 wineries located in Germany, the USA, New Zealand and Australia. The results show that Facebook is the main platform that wineries use to engage with consumers, but that the actual reasons social media is used vary. Winery size and the number of hours spent working on social media also varies across respondents and countries. The findings suggest that wineries need to develop a clear purpose for using social media and then adapt to the needs of the consumers in their respective markets. Keywords: Social media, Wine, Consumer interaction, International comparison